(untitled) (Journal on Geoinformatics, Nepal, 2005)
In this paper the study of two digital terrain model are carried out and to some extent the comparison are made in between them. In the past few years TIN has become increasingly popular perhaps due to the increasing popularity of the Geographic Information System, that can handle the TIN structure and the increasing interest in the visualization of three dimensional objects, but in the contrary there are few investigations carried out in the selection of vertices for TIN from irregularly spaced data such as contours; due to the lack of study in this field the fruitful comparison cannot be achieved. Therefore several trial and error experiments have to be carried out in order to predict the best result.